Moving On as a Key Part of Recovery: What issues arise for Service Users when moving from mental health units into community care? - Antony , Daly (International Journal of Psychosocial Rehabilitation, 2015)
Accommodation for long-term and enduring mental health patients experiencing psychosis has traditionally been provided within statutory provision such as hospitals and wards-in-the-community. More recently this picture has begun to change and many patients have moved out into community-based settings. Recently, in one London borough, 15 clients of the local community rehabilitation team moved out of the ward-in-the-community and into privately-run residential care settings. Following the move the psychology staff on the team conducted a service evaluation to explore Service User experience, to try to understand from a client perspective what such a move was like and to consider ways to improve client experience in the future. This paper presents the outcomes and makes some recommendations for improving the move-on experience for this client group.